Coronal Microleakage in Root Canals Obturated with Lateral Compaction, Warm Vertical Compaction and Guttaflow System - Mohsen Aminsobhani; Abdollah Ghorbanzadeh; Behnam Bolhari; Noushin Shokouhinejad; Sholeh Ghabraei; Hadi Assadian; Marzieh Aligholi (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2010)
INTRODUCTION: Root canal obturation seals the root canal system to prevent re-entry and/or growth of microorganisms. The provision of an appropriate restoration to coronally seal the access cavity affects the success of endodontic treatment. The purpose of this study was to evaluate the coronal microbial leakage in root canals that were either filled by lateral compaction, GuttaFlow or warm vertical compaction. MATERIALS AND METHODS: In this ex vivo study, 80 single-rooted human extracted teeth were randomly divided into three experimental groups (n=20) and two positive and negative control groups (n=10). The teeth in experimental groups were obturated with cold lateral compaction, GuttaFlow system or warm vertical compaction techniques. After sterilization of the whole system with gamma-ray, saliva leakage was tested using a split-chamber model. Specimens were monitored every 24 hours for 30 days. The data were analyzed using log-rank and Kaplan-Meier survival analysis tests. RESULTS: There were no significant differences in impeding saliva leakage between the three experimental groups (P>0.05). CONCLUSION: Under the conditions of this ex vivo study, it can be concluded that the sealing ability of cold lateral compaction, warm vertical compaction and GuttaFlow system was comparable.